2019
DOI: 10.1208/s12249-018-1281-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Protein Content and Number of Aggregates in Monoclonal Antibody Formulation After Large-Scale Freezing

Abstract: Cryoconcentration of an in-house IgG 1 and number of aggregates in a formulation containing trehalose were determined in dependence on freezing protocol and volume. Morphology changes of ice crystals depending on cooling rates were captured by optical cryomicroscopy (OCM) images. UV-Vis and affinity chromatography (ALC) was used to determine protein content and size-exclusion chromatography (SEC) for detection of aggregates. Cooling to − 80°C rather than − 20°C is beneficial in avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
5
21
0
Order By: Relevance
“…These changes are a result of the temperature dependence of the pH value and phosphate crystallization [24], which may have also effects on the titer/conductivity relation. Furthermore, applications of surface microelectrodes in the solid ice state may be reasonable to get high local information about protein concentrations and especially enrichment hot spots as shown in literature [21,31]. Bradford results are very similar to the HPLC titer.…”
Section: Ifr As Key Parameter For Freeze/thawing Experimentsmentioning
confidence: 66%
See 1 more Smart Citation
“…These changes are a result of the temperature dependence of the pH value and phosphate crystallization [24], which may have also effects on the titer/conductivity relation. Furthermore, applications of surface microelectrodes in the solid ice state may be reasonable to get high local information about protein concentrations and especially enrichment hot spots as shown in literature [21,31]. Bradford results are very similar to the HPLC titer.…”
Section: Ifr As Key Parameter For Freeze/thawing Experimentsmentioning
confidence: 66%
“…Especially in phosphate-based buffers, this crystallization effect results in high deviations from the set pH upon freezing. All these effects are considered to affect protein stability and promote aggregation of proteins during freezing [8,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Freezing is typically slower and less controlled, and hydrostatic pressure can build up causing the bottles to deform or rupture (6). Some of these adversities are associated with the cooling of the liquid phase at the air-liquid interface, which causes the top of the liquid to freeze first, forming an ice crust, enclosing the remaining liquid phase (6,7). As the enclosed liquid freezes, the liquid phase is pushed through the ice crust towards the air interface, creating an ice mound (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these adversities are associated with the cooling of the liquid phase at the air-liquid interface, which causes the top of the liquid to freeze first, forming an ice crust, enclosing the remaining liquid phase (6,7). As the enclosed liquid freezes, the liquid phase is pushed through the ice crust towards the air interface, creating an ice mound (7,8). It has been shown that this ice mound is almost pure ice and rich in entrapped air bubbles, and therefore, it is a region of high interfacial stress for proteins, which has been correlated with higher aggregation of monoclonal antibodies (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation